The Effects of Public Policy on Organizational Isomorphic Behaviors and Relationship Marketing Strategies: A Case of Life Insurance Companies in Shandong Province, China - Liu, Jingdong; Submahachok, Pattsornkun; Panyasiri, Chaiyanant; Praditsangthong, Pattamet (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aimed to examine (1) the impact of public policy on organizational isomorphic behaviors within China's life insurance industry; (2) the effect of such isomorphic behaviors on relationship marketing strategies; and (3) the pathway through which public policy ultimately influences marketing efficiency. A mixed-methods approach was employed, comprising quantitative survey data from 425 respondents and in-depth interviews with 12 senior managers from life insurance companies in Shandong Province, selected via quota sampling. Data were analyzed using descriptive statistics, structural equation modeling (SEM), and content analysis. The findings revealed that public policies significantly shape organizational isomorphic behaviors through coercive, mimetic, and normative mechanisms, which in turn influence the adoption and adaptation of relationship marketing strategies, ultimately affecting marketing efficiency. This study contributes to institutional theory and resource dependence theory by elucidating the mediating role of isomorphism in the policy-marketing efficiency nexus, offering practical implications for insurers and policymakers.